2020
DOI: 10.1136/jitc-2020-001128
|View full text |Cite
|
Sign up to set email alerts
|

PODO447: a novel antibody to a tumor-restricted epitope on the cancer antigen podocalyxin

Abstract: BackgroundThe success of new targeted cancer therapies has been dependent on the identification of tumor-specific antigens. Podocalyxin (Podxl) is upregulated on tumors with high metastatic index and its presence is associated with poor outcome, thus emerging as an important prognostic and theragnostic marker in several human cancers. Moreover, in human tumor xenograft models, Podxl expression promotes tumor growth and metastasis. Although a promising target for immunotherapy, the expression of Podxl on normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…Previously we showed that PODO447 exhibits high affinity for tumor-specific glycoepitopes using a well-characterized printed glycan array ( 32 , 41 ). One limitation of these arrays, however, is that they present glycostructures in isolation and not in the context of their normal attachment to proteins or lipids ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we showed that PODO447 exhibits high affinity for tumor-specific glycoepitopes using a well-characterized printed glycan array ( 32 , 41 ). One limitation of these arrays, however, is that they present glycostructures in isolation and not in the context of their normal attachment to proteins or lipids ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were resuspended in 100 μl blocking buffer (FACS buffer, 1 μg/ml of anti-CD16/CD32 (clone 2.4G), 2% rat serum) for 20 min at 4°C in the dark, then spun at 394 g for 4 min and incubated in 100 μl primary antibody (Ab) solution for 30 min at 4°C in the dark. Rabbit-PODO83 ( 16 ) (2 μg/ml); and either rabbit or chimeric PODO447 ( 32 ) (5 μg/ml) were used to detect Podxl. Biotinylated pan-lectenz lectin (1 μg/ml, Lectenz-Bio #SK0501B) was used to detect sialylated complex glycans.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mucin domains also exist in proteins outside of the 21 canonical mucins ( Fig 1A ). For example, CD43 on the surface of leukemia cells selectively interacts with the glyco-immune checkpoint receptor Siglec-7 through its N-terminal mucin domain 16 ; mucin domain-containing splice variants of CD44 (CD44v) serve as cancer cell markers relative to the ubiquitously expressed standard isoform 17 ; CD45 mucin domains act as suppressors of T-cell activation 18 ; mucin domain O-glycosylation on PSGL-1 is required for leukocyte-endothelial interactions 19 ; and aberrant regulation of mucin domains in podocalyxin and SynCAM1 are implicated in a variety of cancers 20,21 . In all of these cases, shared functional attributes of mucin domains impart structural and biophysical properties relevant to their biology.…”
Section: Introductionmentioning
confidence: 99%